2005
DOI: 10.2174/1573400054065578
|View full text |Cite
|
Sign up to set email alerts
|

mGlu5 Receptors: Neuroanatomy, Pharmacology, and Role in Drug Addiction

M. Olive

Abstract: Over the past half century, most studies investigating the neural substrates of drug addiction have focused on the mesolimbic dopamine reward circuitry. Yet recent evidence suggests a critical role for glutamate neurotransmission in addiction-related behaviors. Glutamate receptors, both ionotropic and metabotropic, are widely expressed throughout the central nervous system. Dissection of the role of individual glutamate receptor subtypes in addictive processes has been aided by the development of pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 161 publications
(219 reference statements)
0
17
0
Order By: Relevance
“…Further studies are needed to determine whether dysregulation of this signaling pathway contributes to disorders of excessive ethanol consumption such as alcohol abuse and alcoholism. Although it has been demonstrated that mGluR5 also plays an important role in the reinforcing and behavioral effects of other drugs of abuse such as cocaine and nicotine (Kenny and Markou, 2004;Olive, 2005), no studies to date have examined the role of PKC⑀ activity in modulation of cocaine and nicotine self-administration as well as behavioral and neural plasticity induced by these drugs. Such studies should provide a more detailed understanding of the cellular substrates underlying drug addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to determine whether dysregulation of this signaling pathway contributes to disorders of excessive ethanol consumption such as alcohol abuse and alcoholism. Although it has been demonstrated that mGluR5 also plays an important role in the reinforcing and behavioral effects of other drugs of abuse such as cocaine and nicotine (Kenny and Markou, 2004;Olive, 2005), no studies to date have examined the role of PKC⑀ activity in modulation of cocaine and nicotine self-administration as well as behavioral and neural plasticity induced by these drugs. Such studies should provide a more detailed understanding of the cellular substrates underlying drug addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have examined the role of ionotropic glutamate receptor subtypes (Tzschentke and Schmidt, 2003;Kalivas, 2004), there is increasing evidence that metabotropic glutamate receptors (mGluRs) also play an important role in drug-related behaviors (Kenny and Markou, 2004;Olive, 2005). For example, mice lacking the type 5 mGluR (mGluR5) show dramatically reduced levels of cocaine self-administration and cocaineinduced hyperactivity (Chiamulera et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These investigators further confirmed a role for mGlu 5 receptors in regulating cocaine self-administration by demonstrating that intravenous administration of the mGlu5 receptor antagonist 2-methyl-6-(phenylethynyl)pyridine hydrochloride (MPEP) dose-dependently reduced cocaine self-administration without producing non-specific motor effects (as indicated by a lack of alteration in the rate of lever pressing). This pivotal study provided the first evidence that either genetic or pharmacological inhibition of mGlu 5 receptor function reduces the reinforcing effects of cocaine, and has provoked a wealth of speculation that suggested that mGlu 5 receptor antagonists may prove useful in treating drug addiction in humans (Bird and Lawrence, 2009b; Carroll, 2008; Cryan et al, 2003; Heilig and Egli, 2006; Jaeschke et al, 2008; Jupp and Lawrence, 2009; Kenny and Markou, 2004; Olive, 2005; 2009a; Spooren et al, 2001). Subsequent studies examining the effects of inhibition of Group I mGlu receptor function on the rewarding and reinforcing properties of cocaine and other drugs of abuse, and relapse-like behaviors, will now be reviewed.…”
Section: Reductions In Drug Intake Reward and Relapse Produced Bmentioning
confidence: 99%
“…Systemic administration of mGlu 5 receptor antagonists such as MPEP or the more selective compound 3-((2-Methyl-4-thiazolyl)ethynyl)pyridine (MTEP) reduces operant self-administration of cocaine (Chiamulera et al, 2001; Iso et al, 2006; Kenny et al, 2005; Kenny et al, 2003; Lee et al, 2005; Martin-Fardon et al, 2009; Platt et al, 2008; Tessari et al, 2004), nicotine (Paterson et al, 2003; Tessari et al, 2004), heroin (van der Kam et al, 2007), ketamine (van der Kam et al, 2007), methamphetamine (Gass et al, 2009), and ethanol (Backstrom et al, 2004; Gupta et al, 2008; Hodge et al, 2006; Lominac et al, 2006; McMillen et al, 2005; Olive et al, 2005; Schroeder et al, 2005). The ability of MPEP and MTEP to suppress drug self-administration is due, at least in part, by a reduction in the reinforcing efficacy of the self-administered drug, as it has been shown that MPEP and MTEP can reduce breakpoints for drug self-administration on a progressive ratio schedule of reinforcement (Besheer et al, 2008b; Gass et al, 2009; Paterson and Markou, 2005).…”
Section: Reductions In Drug Intake Reward and Relapse Produced Bmentioning
confidence: 99%
“…For example, mice lacking the mGlu5 receptor gene do not self-administer cocaine and are indifferent to its locomotor stimulant effects (Chiamulera et al, 2001), display abnormalities in the induction of synaptic plasticity associated with learning and memory (Jia et al, 1998) and lack certain physiological responses to stress (Brodkin et al, 2002a). Pharmacological studies in animals using systemically active mGlu5 antagonists such as 2-methyl-6-(phenylethynyl)-pyridine (MPEP) and 3-[(2-methyl-1,3-thiazol-4-yl)ethynyl]-pyridine (MTEP) Gasparini et al, 1999) have revealed potential beneficial effects of mGlu5 antagonists in the treatment of disorders such as depression, anxiety, epilepsy, Parkinson's disease, alcoholism and drug addiction (Conn, 2003;Gass and Olive, 2008;Kenny and Markou, 2004;Lea and Faden, 2006;Olive, 2005;Palucha and Pilc, 2007;Slassi et al, 2005;Spooren and Gasparini, 2004;Swanson et al, 2005;Witkin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%